Optimizing Sample Warehouse Layout At PT BIJ: Comparative Study Of Dedicated And Class-Based Storage - Arif, Muhammad Wildan; Andesta, Deny (Advance Sustainable Science, Engineering and Technology, 2024)
PT. BIJ is an analytical laboratory services company, therefore PT. BIJ needs a good warehouse to be able to accommodate the samples it has PT. BIJ experienced problems with sample storage. Therefore, it is necessary to improve the sample storage system to make it easier to find samples to be analyzed. Using the Dedicated Storege and Class Base Storage methods will help provide grouping for each type of sample and place the samples in the right place so that the sample travel distance is shorter. The results of the research carried out can be obtained that the initial travel distance is 262.98 meters, while the proposed dedicated storage distance is 163.19 meters and the proposed basic class storage distance is 149.95 meters, so there is the largest percentage difference of 42.89%. So it can be concluded that using the class base storage method is better than the dedicated storage method.